Ronggeng: Genealogi Perempuan Penari Dari Masa Kolonial Hingga Era Mutakhir - S.Sn., M.Sn., Masyuning; Atang Suryaman; Pepep Didin Wahyudin (LP2M ISBI Bandung, 2025)
In the current discourse of performing arts, ronggéng has been specified or narrowed down to mean only female dancers. The opposite of ronggéng is known as